Automated Handwritten Equation Solver - Shereen A. Hussien; Ahmed M. Abd el Azim; Ahmed Hagag (International Journal of Advanced Science and Computer Applications, 2025)
Mathematics has an important role in person’s life, so solving the mathematical equations is an essential.  Solving mathematical expressions is not restricted to just students but also for mathematicians, physicists and scientists. Solving the mathematical equations is an interesting process.The traditional method of solving math expressions is unsatisfactory as the user should learn different rules and approaches for each mathematical equation. Also, these methods may take long time in complex or obscure problems which makes them subject to user errors and mistakes. The challenging in mathematical expressions must be written in a specific format, users prefer to write them on paper as an easy entering way than other computerized tools. This paper used the technology to introduce a new method over the traditional one using pen and paper.  The equation handwriting easiness is blended (merge/integrate) with the advanced computer technologies speed to solve the equations with flexible robust way. An interface introduces that allows capturing the equations contained in an image then solving it without making the user dive into the complex rules. Various types of equations could be entered to this application (linear/nonlinear/quadratic) with achieving a convenient accuracy 95.7%.